Systematic theoretical investigation of geometries, stabilities and magnetic properties of iron oxide clusters (FeO)nμ (n = 1–8, μ = 0, ±1): insights and perspectives. Issue 9 (23rd December 2014) - Ju, Meng; Lv, Jian; Kuang, Xiao-Yu; Ding, Li-Ping; Lu, Cheng; Wang, Jing-Jing; Jin, Yuan-Yuan; Maroulis, George
Abstract : The structural and magnetic properties of neutral and charged (FeO) n μ ( n = 1–8, μ = 0, ±1) clusters have been studied using an unbiased CALYPSO structure searching method. Abstract : The structural properties of neutral and charged (FeO) n μ ( n = 1–8, μ = 0, ±1) clusters have been studied using an unbiased CALYPSO structure searching method. As a first step, an unbiased search relying on several structurally different initial clusters has been undertaken. Subsequently, geometry optimization by means of density-functional theory with the Perdew and Wang (PW91) exchange–correlation functional is carried out to determine the relative stability of various candidates for low-lying neutral, anionic and cationic iron oxide clusters obtained from the unconstrained search. It is shown that the mostly equilibrium geometries of iron oxide clusters represent near planar structures for n ≤ 3. No significant structural differences are observed between the neutral and charged iron oxide clusters beyond sizes with n = 6. The relative stabilities of (FeO) n μ clusters for the ground-state structures are analyzed on the basis of binding energies and HOMO–LUMO gaps. Our theoretical results confirm that the binding energies of neutral and anionic (FeO) n 0/− tend to increase with cluster size. Cationic (FeO) n + exhibits a slight downward trend. It is worth noticing that (FeO)5 and (FeO)4 −/+ are the most stable geometries for (FeO) n μ ( n = 1–8, μ = 0, ±1) clusters. Lastly, an evident local oscillation of magnetic behavior is present in the most stable (FeO) n μ ( n = 1–8, μ = 0, ±1) clusters, and the origin of this magnetic phenomenon is analyzed in detail.